Coupled Translational–Rotational Stability Analysis of a Submersible Ocean Current Converter Platform Mooring System under Typhoon Wave - Shueei-Muh Lin; Didi Widya Utama; Chihng-Tsung Liauh (Journal of Marine Science and Engineering, 2023)
This study proposes a mathematical model for the coupled translational–rotational motions of a mooring system for an ocean energy converter working under a typhoon wave impact. The ocean energy convertor comprises two turbine generators and an integration structure. The configuration of the turbine blade and the floating platform is designed. The two turbine blades rotate reversely at the same rotating speed for rotational balance. If the current velocity is 1.6 m/s and the tip speed ratio is 3.5, the power generation is approximately 400 kW. In the translational and rotational motions of elements under ocean velocity, the hydrodynamic parameters in the fluid–structure interaction are studied. Initially, the hydrodynamic forces and moments on the converter and the platform are calculated and further utilized in obtaining the hydrodynamic damping and stiffness parameters. The 18 degrees of freedom governing equations of the mooring system are derived. The solution method of the governing equations is utilized to determine the component’s motion and the ropes’ dynamic tensions. In the mooring system, the converter is mounted under a water surface at some safe depth so that it can remain undamaged and stably generate electricity under typhoon wave impact and water pressure. It is theoretically verified that the translational and angular displacements of the converter can be kept small under the large wave impact. In other words, the water pressure on the converter cannot exceed the predicted value. The relative flow velocity of the convertor to the current is kept fixed such that the power efficiency of convertor can be maintained as high. In addition, the dynamic tension of the rope is far less than its breaking strength.